Legal Protection Against Children of Consanguineous Marriages - Ariany, Farida; Aminullah, Aminullah; Fitriatun, Erna (Lembaga Penelitian dan Pendidikan Mandala, 2025)
A secret marriage is considered invalid by the state, therefore, children born from this marriage are considered as children born out of wedlock. This is different from the religious perspective. This opinion is based on article 43 paragraph (1) of the Marriage Law which states that